PENGARUH PROFESSIONAL SELF EFFICACY, LIFE SATISFACTION DAN BURNOUT TERHADAP JOB PERFORMANCE YANG DIMEDIASI OLEH WORK ENGAGEMENT (STUDI EMPIRIS PADA PERAWAT RUMAH SAKIT TMC) - Widjaya, Indry; Achmadi, Hendra (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
The purpose of this research is to examine the influence of professional self-efficacy, life satisfaction, and burnout, mediated by work engagement, on job performance among nurses working at TMC Hospital in Tasikmalaya. This study is quantitative and survey-based. Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized to analyze empirical data obtained through simple random sampling. A total of 166 samples were collected and assessed via distributed online questionnaires. The research results indicate that ten hypotheses were tested, two of which demonstrated negative and significant coefficient values in line with the hypotheses. Seven hypotheses showed positive and significant coefficient values as hypothesized. However, one hypothesis yielded non-significant results. The strongest direct influence on job performance was found to originate from work engagement and professional self-efficacy (coefficients: 0.338 and 0.24). There was evidence of a negative impact from burnout on job performance (-0.223). Therefore, the outcomes of this study support that engagement, self-efficacy, and fatigue management can enhance nurse performance, presenting novel applications towards nurse performance. This research model demonstrated moderate predictive accuracy and relevance, indicating potential for further exploration in future research. The research findings offer managerial implications concerning human resource management, particularly in hospital nursing, and recommendations for future researchers regarding sample size, inclusion criteria, and geographical scope. Keywords: Professional self-efficacy, life satisfaction, burnout, work engagement, job performance